Ethics Meetings in Support of Good Nursing Care: some practice-based thoughts - de Casterlé, Bernadette Dierckx (Nursing ethics, 2002)
The purpose of this article is to clarify both the role of nurses in ethics meetings and the way in which ethics meetings can function as a catalyst for good nursing care. The thoughts presented are practice based; they arose from our practical experiences as nurses and ethicists with ethics meetings in health care organizations in Belgium. Our reflections are written from the perspective of the nurse in the field who is participating in (inter)professional ethical dialogue. First, the difficulties that nurses experience while participating in ethics meetings are described. Then the possibilities for support of nurses in their ethical responsibility are explored.